Comparison of Two Obturation Techniques on Adhesion and Proliferation of Human Periodontal Ligament Fibroblasts - Vázquez Vázquez, Febe C.; Avalos Piña, Lourdes Y.; Rodríguez Hidalgo, Alejandra; Pozos-Guillén, Amaury; González-Alva, Patricia; Montero-Aguilar, Mauricio; Chavarría-Bolaños, Daniel; Álvarez Pérez, Marco A. (Odovtos - International Journal of Dental Sciences, 2022)
The present study aimed to compare the adhesion and proliferation of human periodontal ligament fibroblasts (hPDL) in transverse sections of the teeth sealed with two different obturation techniques, BioRoot RCS/hydraulic obturation (HO) and AH-Plus/continuous-wave condensation (CWC). The techniques were tested using an in vitro model to simulate the interaction between periodontal tissues and the materials. The root canals were instrumented and sterilized. A total of 15 samples were obturated with BioRoot RCS/HO and 15 samples with AH-Plus/CWC. Then, roots were sectioned to obtain obturated teeth slices, and hPDL cells were seeded onto the root slices. The results were obtained at intervals of 4 and 24 h for cell adhesion; and at 3,7,14, and 21 days for cell proliferation. Empty cell culture plates were use as controls. The cell adhesion was increased at 4 and 24 h for both groups, with an increased response observed in the BioRoot RCS/HO group (p<0.05). The difference in cell proliferation was also found between experimental groups. After 14 days of culture, BioRoot RCS/HO group showed an increase response than control and AH-Plus/CWC groups (p<0.05), and after 21 days both groups behaved better than control group, with an increased response observed in the BioRoot RCS/HO group. This study demonstrated that both root canal sealers allow the attach and growth of periodontal ligament fibroblasts, with an increased biological response in the BioRoot RCS/HO group.